Revisiting the EU cybersecurity strategy: A call for EU cyber diplomacy - Annegret Bendiek; Matthias C. Kettemann (Stiftung Wissenschaft und Politik (SWP), 2021)
In December 2020, the European Union (EU) presented its new strategy on cybersecurity with the aim of strengthening Europe's technological and digital sovereignty. The document lists reform projects that will link cybersecurity more closely with the EU's new rules on data, algorithms, markets, and Internet services. However, it clearly falls short of the development of a European cyber diplomacy that is committed to both 'strategic openness' and the protection of the digital single market. In order to achieve this, EU cyber diplomacy should be made more coherent in its supranational, democratic, and economic/technological dimensions. Germany can make an important contribution to that by providing the necessary legal, technical, and financial resources for the European External Action Service (EEAS).
Keywords: 320